Acerca del carácter irreductible de la mens humana en Nicolás de Cusa: unidad y número - Claudia D’Amico (Franciscanum, 2018)
Nicholas of Cusa elaborates the doctrine of the human spirit as a Metaphysics of Subjectivity. The Cusanus shows that the being of mind is its own operation and its own deployment that becomes either a form or a conjectural world entity. The deployment of every mind in a symbolic world has a unique and irreducible character. In order to elaborate this doctrine that advances modernity, the Cusanus responds to the relation between unit and number, which comes from the Platonic-Pythagorean Tradition.